1989
DOI: 10.1161/01.res.65.5.1306
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective block of cardiac sodium channels by RAC109 in single guinea pig ventricular myocytes.

Abstract: The effects of the optical stereoisomers of the local anesthetic RAC109 (RAC109-I and RAC109-II) on sodium current in isolated guinea pig ventricular myocytes were investigated by use of the whole-cell variation of the patch-clamp technique. RAC109-I and RAC109-1I produced similar levels of tonic block, but RAC109-I produced a significantly larger usedependent block on repetitive pulsing to potentials positive to -60 mV. Definition of the time courses of block development at -20 mV and recovery at -140 and -16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Many LA are racemates whose constituents often differ pharmacologically, in particular in binding to the receptor (182, 515) but also in unbinding leading to differences in use dependence (86,105,459). No stereoselective action on TTX-resistant channels was observed (51).…”
Section: Local Anesthetics Preferentially Bind To Inactivated Channelsmentioning
confidence: 99%
“…Many LA are racemates whose constituents often differ pharmacologically, in particular in binding to the receptor (182, 515) but also in unbinding leading to differences in use dependence (86,105,459). No stereoselective action on TTX-resistant channels was observed (51).…”
Section: Local Anesthetics Preferentially Bind To Inactivated Channelsmentioning
confidence: 99%
“…Modulation of cardiac sodium channel function is thought to be mediated by binding of the drugs to a receptor site directly associated with the ion channel (Catterall, 1987;Sheldon et al, 1987). Stereoselectivity of this putative binding site has been demonstrated in experiments with the local anaesthetic RAC 109 (Yeh, 1980;Postma & Catterall, 1983;Clarkson, 1986) as well as the antiarrhythmic tocainide . A comparative study, however, revealed considerable stereospecific differences in the binding of type 1 antiarrhythmics to cardiac sodium channels, and disopyramide as well as flecainide were found to bind nonstereoselectively (Hill et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…R (+)bupivacaine was about 1.6 times more efficient in blocking Na + channels than the other enantiomer (Fig. (A)) …”
Section: Stereoselective Interactions Between Local Anesthetic‐like Dmentioning
confidence: 96%
“…2(A)). 6,22 Different amino acid substitutions at position N434 (DI-S6) led to an increase or to a decrease in bupivacaine potency that depended on the physicochemical characteristics of the amino acid introduced. Thus, the potency of bupivacaine enantiomers was increased in N434 mutant Nav1.4 channels in which the native asparagine was substituted by amino acids containing an aromatic group (phenylalanine, tryptophan, or tyrosine), a polar group (cysteine), or a negative charge (aspartic) and decreased in a mutation containing a positive charge (lysine).…”
Section: Stereoselective Interactions Between Local Anesthetic-like Dmentioning
confidence: 99%